A new hybrid fuzzy proportional-derivative phase-locked-loop controller for DC servomotor speed control - Sooraksa, Pitikhate; Li, Chung Wai; Damrongporn, Phuwanat (My University, 2007)
Some research work has been heading to the promising direction of enhancing conventional controllers with various powerful intelligent features. In this pursuit, the paper presents a new fuzzy-based phase-locked loop (FPLL) controller for DC servomotor speed control. Fuzzy logic provides fast response and enhances robustness of the system while PLL control gives excellent steady state system performance. Unlike the past literatures, this fuzzy-based controller employs a proportional-derivative (FPD) controller, which is constructed precisely based on rigorous mathematical analysis instead of using look-up tables, with stability guaranteed. Simulation and experimental results have signified the design objectives and been accomplished. The proposed new fuzzy-based PLL controller gives a better dynamic performance compared to a conventional PID controller. Copyright © 2007 Watam Press.
Keywords: Fuzzy control; Motor control; Phase-locked loop; PID control